2021
DOI: 10.3390/life11020167
|View full text |Cite
|
Sign up to set email alerts
|

Post-Infectious Guillain–Barré Syndrome Related to SARS-CoV-2 Infection: A Systematic Review

Abstract: Background. Guillain-Barré syndrome (GBS) is the most common cause of flaccid paralysis, with about 100,000 people developing the disorder every year worldwide. Recently, the incidence of GBS has increased during the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) epidemics. We reviewed the literature to give a comprehensive overview of the demographic characteristics, clinical features, diagnostic investigations, and outcome of SARS-CoV-2-related GBS patients. Methods. Embase, MEDLINE, Google Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…In contrast to the presence of peculiarities of our cases, in a recent epidemiological and cohort study recorded by Keddie et al (33), they compared COVID-19 (definite or probable)and non-COVID-19-associated GBS patients and found no significant differences in the pattern of weakness, time to nadir, neurophysiology, or outcome. Two other systematic reviews by Abu-Rumeileh et al (11) and Sansone et al (34) showed that the clinical picture of COVID-19-associated GBS seems to resemble that of classic GBS or Zika virus-associated GBS.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to the presence of peculiarities of our cases, in a recent epidemiological and cohort study recorded by Keddie et al (33), they compared COVID-19 (definite or probable)and non-COVID-19-associated GBS patients and found no significant differences in the pattern of weakness, time to nadir, neurophysiology, or outcome. Two other systematic reviews by Abu-Rumeileh et al (11) and Sansone et al (34) showed that the clinical picture of COVID-19-associated GBS seems to resemble that of classic GBS or Zika virus-associated GBS.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, the rapid development of the pandemic may have significantly influenced the general attitude towards vaccination. In the meantime, it is known that COVID‐19 infection may trigger GBS 37,38 . Also in addition, different kinds of COVID‐19 vaccines have been reported to have the potential to trigger GBS 39‐42 …”
Section: Discussionmentioning
confidence: 99%
“…MRI can reveal thickening of the affected nerve roots and avid contrast enhancement of the conus medullaris and cauda equina, with preferential enhancement of the ventral nerve roots[ 141 ]. The fact that viral RNA has not been identified on cerebrospinal fluid analysis in affected patients suggests that injury occurs via an immune-mediated mechanism, such as molecular mimicry or antibody precipitation, rather than by direct viral insult[ 142 ]. A similar mechanism has been proposed for rare cases of new-onset myasthenia gravis developing in the setting of COVID-19[ 143 ].…”
Section: Extrapulmonary Manifestationsmentioning
confidence: 99%